Selected motor ability components of field hockey goalkeepers at different levels of participation - Singh, A. K. (Journal of Physical Education Research, 2015)
The purpose of the study was to compare selected motor ability components of field hockey goalkeepers at different levels of participation. 45 male field hockey goalkeepers were selected for the purpose of the study. Out of 45 subjects, 15 subjects each were selected from inter-collegiate, inter-university and national level. The motor ability components selected in this were flexibility, orientation ability, balance ability and reaction ability. Before the collection of data the purpose and procedure of the tests items were explained to the subjects, and given sufficient time for warm-up before testing. Adequate demonstrations with regard selected test were also given. The necessary data was collected by administering various tests for the chosen variables. ANOVA (analysis of variance) technique was used to compare the means of different levels of participations followed by LSD (least significant difference) wherever applicable. The level of significant to determine the significant difference was set at 0.05 levels. The results of the study showed that significant difference existed in flexibility, orientation ability, balance ability and reaction time ability among senior national, inter-university and inter-collegiate level of field hockey goalkeepers.